NANOTECHNOLOGY-DRIVEN INNOVATIONS IN HYPERTENSION MANAGEMENT: FORMULATION STRATEGIES, CHALLENGES, AND FUTURE DIRECTIONS - SAHOO, UDAYA KIRAN; VIDYACHARAN S; PRITAM KAYAL; JAWAHAR N (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Abstract: Hypertension creates a worldwide public health challenge that significantly increases risks for cardiovascular diseases, strokes, and kidney failure. The standard therapeutic treatments comprising ACE inhibitors and beta blockers struggle with several problems, including limited solubility together with short half-life duration along with unwanted effects causing reduced patient treatment adherence. Drug delivery systems powered by nanotechnology offer innovative solutions to address the problems through techniques like nanoparticles together with liposomes and microneedles. Nanotechnology-based drug delivery systems enhance drug effectiveness and improve stability while enabling precise drug distribution, which leads to reduced first-pass metabolism and lowered systemic side effects. Drug delivery according to circadian rhythms achieves better therapeutic effects at reduced risks. Researchers have developed two new approaches for medication delivery that utilise intranasal systems together with dissolvable microneedle patches for providing fast and easy administration capability. Hypertension management through nanotechnology applications delivers a transformational method that addresses numerous limitations of existing treatment approaches. Although the preclinical data holds promise, the clinical implementation of such innovative systems faces substantial obstacles. The implementation of nanotechnology in regular clinical practices will reshape hypertension treatment through performance-enhanced approaches that offer tailor-made patient-centred management.